Free‐Standing Functionalized Graphene Oxide Solid Electrolytes in Electrochemical Gas Sensors. (2nd February 2016) - Jiang, Gaopeng; Goledzinowski, Maciej; Comeau, Felix J. E.; Zarrin, Hadis; Lui, Gregory; Lenos, Jared; Veileux, Alicia; Liu, Guihua; Zhang, Jing; Hemmati, Sahar; Qiao, Jinli; Chen, Zhongwei
Abstract : A free‐standing sulfonic acid functionalized graphene oxide (fSGO)‐based electrolyte film is prepared and used in an electrochemical gas sensor, an alcohol fuel cell sensor (AFCS), for the detection of alcohol. The fSGO electrolyte film‐based AFCS detects ethanol vapor with excellent response, linearity, and sensitivity, since it possesses a high proton conductivity (58 mS cm −1 at 55 °C). An ethanol detection limit level as low as 25 ppm is achieved and high selectivity for ethanol over acetone is demonstrated. These results do not only show the promising potential of fSGO films in an electrochemical gas sensors, specifically a portable breathalyzer, but also open an alternative pathway to investigate the application of graphene derivatives in the field of gas sensors. Abstract : An new type of electrochemical gas sensor, employing a free‐standing film of sulfonic acid functionalized graphene oxide (fSGO) as the solid electrolyte, is developed. Based on the design of alcohol fuel cell sensors (AFCSs), the developed sensor detects alcohol with excellent sensor response, linearity, sensitivity, and selectivity, promising its implementation into portable devices.